The phonology and morphology of Halfway River Beaver. - Randoja, Tiina Kathryn. (University of Ottawa (Canada), 1990)
This dissertation is an examination of word formation and the phonological properties of the verb in Halfway River Beaver (HRB), a Northern Athapaskan language of British Columbia. Due to various types of discontinuous dependencies between verb prefixes, I adopt the traditional analysis of the Athapaskan verb into verb theme, verb base, and verb form (Sapir and Hoijer 1967, among others) to determine the sequence of affixation in the morphology. The resulting representation structures prefixes in a way which is vastly different from their surface ordering; the differences seem bizarre, as they are not encountered in non-Athapaskan languages. I propose a mapping protocol to arrive at the correct surface sequence, whereby affixes are inserted into a thematic template. It is argued that this template is a motivated structure, because it represents both the theme, which is the lexical entry of the verb, and the division of the verb into phonological rule domains. Two aspects of verb prefix phonology are considered. First, I account for the phonological similarity of two nonadjacent rule domains of the surface verb, the disjunct and the stem domains, in terms of the mapping protocol developed earlier. Secondly, I investigate the very complex and seemingly arbitrary phonological alternations undergone by prefixes in the conjunct domain, which intervenes between the disjunct and stem domains. These alternations are shown to be systematic in an analysis which adopts the notions of syllable template mapping and extraprosodicity. Conjunct prefix vowels are considered to be mostly epenthetic and vowel quality is seen to be largely predictable. The morphological and phonological analyses are preceded by a chapter which describes the properties of HRB verb prefixes in detail.
Keywords: Language, Linguistics.